Dynamic compression of foam supported plates impacted by high velocity soil - Liu, Tao; Wadley, H.N.G.; Deshpande, V.S. (Elsevier, 2014)
The response of back-supported buffer plates comprising a solid face sheet and foam core backing impacted by a column of high velocity particles (sand slug) is investigated via a lumped parameter model and coupled discrete/continuum simulations. The buffer plate is either resting (unattached) or attached to a rigid stationary foundation. The lumped parameter model is used to construct maps of the regimes of behaviour with axes of the ratio of the height of the sand slug to core thickness and the normalised core strength. Four regimes of behaviour are identified based on whether the core compression ends prior to the densification of the sand slug or vice versa. Coupled discrete/continuum simulations are also reported and compared with the lumped parameter model. While the model predicted regimes of behaviour are in excellent agreement with numerical simulations, the lumped parameter model is unable to predict the momentum transmitted to the supports as it neglects the role of elasticity in both the buffer plate and the sand slug. The numerical calculations show that the momentum transfer is minimised for intermediate values of the core strength when the so-called “soft-catch” mechanism is at play. In this regime the bounce-back of the sand slug is minimised which reduces the momentum transfer. For high values of the core strength, the response of the buffer plate resembles a rigid plate with nearly no impulse mitigation while at low values of core strength, a slap event occurs when the face sheet impinges against the foundation due to full densification of the foam core. This slap event results in a significant enhancement of the momentum transfer to the foundation. The results demonstrate that appropriately designed buffer plates have potential as impulse mitigators in landmine loading situations.